The Effect of 30 Minutes of Swimming Training on VO₂Max in 30-Year-Old Non-Athletes - Akbar, Nur Kholis; Mukti Widodo, Haryo; Yuli Handayani, Heni; Putri Purwoto, Septyaningrum; Himawan, Agus (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
Maximal oxygen volume (VO₂Max) is a major indicator of aerobic capacity and cardiovascular health. At the age of 30 years, there is a gradual decline in cardiorespiratory function if not balanced with adequate physical activity. Swimming training is categorized as a low-impact aerobic activity that involves many muscle groups simultaneously and has the potential to increase VO₂Max in non-athlete populations. This study aims to evaluate the effect of 30-minute swimming training on increasing VO₂Max in 30-year-old non-athlete individuals. The design of this study was a one-group pretest-posttest with a quantitative approach. A total of 20 male subjects aged 30 years (±1 year), who were physically inactive and had no history of chronic disease, participated in a swimming training program for six weeks, three times a week, each for 30 minutes. VO₂Max was measured using a multistage fitness test (beep test) before and after the intervention. Statistical analysis used a paired t-test with a significance level of p <0.05. The results showed a statistically significant increase in VO₂Max (mean pretest = 35.2 ± 3.4 ml/kg/min; posttest = 39.1 ± 3.6 ml/kg/min; p < 0.001), indicating a positive adaptation to aerobic training in water. Regular 30-minute swimming training has been shown to be effective in increasing VO₂Max in non-athlete 30-year-old individuals. This training can be recommended as an efficient and low-risk fitness strategy for the productive age group.